Attrition in the First Three Therapy Lines in Patients with Advanced Breast Cancer in the German Real-World PRAEGNANT Registry - Hartkopf, Andreas D.; Walter, Christina B.; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Fasching, Peter A.; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias W.; Belleville, Erik; Huebner, Hanna; Uhrig, Sabrina; Goossens, Chloë; Link, Theresa; Hielscher, Carsten; Mundhenke, Christoph; Kurbacher, Christian; Wuerstlein, Rachel; Untch, Michael; Janni, Wolfgang; Taran, Florin-Andrei; Michel, Laura L.; Lux, Michael P.; Wallwiener, Diethelm; Brucker, Sara Y.; Fehm, Tanja N.; Häberle, Lothar; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2024)
Background With more effective therapies for patients with advanced breast cancer (aBC), therapy sequences are becoming increasingly important. However, some patients might drop out of the treatment sequence due to deterioration of their life status. Since little is known about attrition in the real-world setting, this study assessed attrition in the first three therapy lines using a real-world registry.Methods Patients with information available on the first three therapy lines were selected from the German PRAEGNANT registry (NCT02338167). Attrition was determined for each therapy line using competing risk analyses, with the start of the next therapy line or death as endpoints. Additionally, a simple attrition rate was calculated based on the proportion of patients who completed therapy but did not start the next therapy line.Results Competitive risk analyses were performed on 3988 1st line, 2651 2nd line and 1866 3rd line patients. The probabilities of not starting the next therapy line within 5 years after initiation of 1st, 2nd and 3rd line therapy were 30%, 24% and 24% respectively. Patients with HER2-positive disease had the highest risk for attrition, while patients with HRpos/HER2neg disease had the lowest risk. Attrition rates remained similar across molecular subgroups in the different therapy lines.Conclusion Attrition affects a large proportion of patients with aBC, which should be considered when planning novel therapy concepts that specifically address the sequencing of therapies. Taking attrition into account could help understand treatment effects resulting from sequential therapies and might help develop treatment strategies that specifically aim at maintaining quality of life.
Keywords: advanced breast cancer; de novo metastatic breast cancer; recurrent breast cancer metastases; clinical trials